Enhancing Magnetic and Magnetotransport Properties by Topotactic Reduction of the Sr 2 Fe 1.33 Mo 0.66 O 6 Double Perovskite - Lopez, Carlos Alberto (2010)
Sr2Fe1.33Mo0.66O6 (alternately written as Sr3Fe2MoO9) perovskite has been prepared in polycrystalline form by thermal treatment, in air, of previously decomposed citrate precursors. This material has been studied by X-ray and neutron powder diffraction (XRPD and NPD), magnetic and transport measurements. At room temperature, the crystal structure is cubic with a = 7.8585(2) Å and V = 485.30(2) Å3, defined in the space group Fm-3m. Magnetic measurements indicate a ferromagnetic ordering below TC = 246 K. As prepared, the sample is an electrical insulator. A topotactic reduction of the stoichiometric sample performed at 600, 700, and 800 °C, in H2/N2 flows, leads to the oxygen-deficient double perovskites, Sr2Fe1.33Mo0.66O6?δ with increasing δ values. The evolution of the crystal structure upon reduction has been studied from XRPD and NPD data. For the sample obtained at 800 °C, exhibiting the largest δ value, the low-temperature evolution from NPD data was investigated between 2 K and 500 K: in all the temperature range the crystal structure is cubic with space group Fmequation imagem; at room temperature a = 7.87060(6) Å and V = 487.555(6) Å3. The magnetic behavior of this reduced sample suggests the presence of ferromagnetic domains characterized by Curie temperatures with TC > 400 K. The conductivity dramatically increases upon H2 reduction. Moreover, this reduced sample exhibits magnetoresistance, as high as 2.5 % at room temp. for H = 5 T. Magnetic and magnetotransport results are consistent with a large component of itinerancy for down-spin Mo t2g electrons, injected through hydrogen reduction.